PENERAPAN METODE ACTIVITY BASED COSTING (ABC) DALAM MENENTUKAN HARGA POKOK PRODUKSI CV INDIGO BIRU BARU KECAMATAN BULU KABUPATEN SUKOHARJO - Rizky Miftahul Jannah; Anita Wijayanti; Purnama Siddi (PROSEDING, 2022)
This study aims to determine the comparison of the application of the cost of production between the methods used in CV. NEW Indigo Biru currently is the traditional method with the activity based costing (ABC) method. The background of this research was made because of several problems faced by the company, especially in facing similar competitors. Given the importance of CV. Indigo Blue New in determining the right cost of production so as to produce an efficient nominal selling price is also one of the strong reasons for writing this research. The method used in this research is a comparative descriptive qualitative research. By using this research method, this study describes an event that occurred and compares the application of production cost calculations between the methods used by the company today and the activity Based Costing method on research objects related to Cost Accounting, especially in calculating the cost of production. The data used by researchers in the form of primary and secondary data. Primary data is in the form of interviews with the research object, secondary data in the form of a recap of production data in December 2022 on CV Indigo Blue New. The results of this study are that there are differences in results between one product and another, and one method to another. this happens because the calculation used by the CV Indigo Blue New company currently has a lower level of accuracy compared to the calculation of the activity based costing (ABC) method in determining the cost of production. This is evidenced by the presence of 2 types of products, namely batik shirts and batik blouses that have decreased in value or undervalue in the final calculation of the cost of production. Therefore, the activity based costing (ABC) method is one of the solutions offered for companies in determining the cost of production Keywords : Cost of Production, Activity Based Costing Method, Method Traditional